CONSUMERS ' THOUGHTS ON RETRO MARKETING: A RESEARCH IN ANTALYA - Mükerrem Oral (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
In the process of information society, the fact that enterprises face global competition in a global market makes it necessary to develop alternative methods in the field of marketing as in other areas. Retro marketing is one of these methods that aim to increase customer satisfaction and can be used as a marketing strategy for businesses. This study focuses on determining the thoughts of consumers on retro marketing and examining the concept of retro marketing in terms of the socio-demographic characteristics of consumers. In line with this purpose, an online questionnaire with easy sampling method was applied to 645 participants living in Antalya. As a result of the study, statistically significant differences were found in the nostalgia sub-dimension according to age and occupation variables in the retro marketing scale.